Measurement of D-+/- production in deep inelastic ep scattering with the ZEUS detector at HERA - Abramowicz, H; Abt, I; Adamczyk, L; Adamus, M; Aggarwa, R; Antonelli, S; Antonioli, P; Antonov, A; Arneodo, M; Arslan, O; Aushev, V; Aushev, Y; et al. (2013)
Charm production in deep inelastic ep scattering was measured with the ZEUS detector using an integrated luminosity of 354 pb-1. Charm quarks were identified by reconstructing D± mesons in the D ± → K∓π±π ± decay channel. Lifetime information was used to reduce combinatorial background substantially. Differential cross sections were measured in the kinematic region 5 < Q 2 < 1000 GeV 2, 0.02 < y < 0.7, 1.5 < p T (D ±) < 15 GeV and |η(D ±)| < 1.6, where Q 2 is the photon virtuality, y is the inelasticity, and p T (D ±) and η(D ±) are the transverse momentum and the pseudorapidity of the D ± meson, respectively. Next-to-leading-order QCD predictions are compared to the data. The charm contribution, F2cc̄, to the proton structure-function F 2 was extracted. © 2013 SISSA.